Comparative Evaluation of Forsus Fatigue Resistant Device and Fixed Twin Block Appliance in the Treatment of Class II Division 1 Malocclusion - Singh, Rakesh Avadesh; Jadhav, Pranita; Kadam, Vighanesh; Jongkey, Lirik; Shroff, Keval; Narkhede, Sameer; Shah, Dhaval (Journal of Neonatal Surgery, 2025)
Introduction:Class II Division 1 malocclusion, commonly caused by a retrognathic mandible, is one of the most frequently encountered orthodontic problems. While traditional removable functional appliances like the Twin Block have shown success in modifying growth, they require high patient compliance. Fixed functional appliances such as the Forsus Fatigue Resistant Device (FRD) offer a solution by providing continuous, compliance-free force. This study compares the clinical efficacy of these two appliances in growing patients. Aim:To evaluate and compare the skeletal, dental, and soft tissue changes induced by Forsus FRD and Fixed Twin Block appliances in the treatment of Class II Division 1 malocclusion in growing individuals. Materials and Methods:A prospective comparative study was conducted on 30 growing patients aged 12–14 years with skeletal Class II Division 1 malocclusion. The patients were divided into two groups: one treated with Forsus FRD and the other with Fixed Twin Block. Pre- and post-treatment lateral cephalograms were analyzed using composite cephalometric analysis, and skeletal, dental, and soft tissue changes were compared. The Pancherz method was used for superimposition. Statistical analyses were performed using paired and unpaired t-tests. Results:Both appliances were effective in correcting Class II malocclusion. The Twin Block group showed greater skeletal changes, including a more significant increase in mandibular length and vertical control. Forsus FRD produced faster results and more pronounced dentoalveolar changes, including upper molar distalization and lower incisor proclination. Both groups exhibited soft tissue improvements, with slightly more favorable outcomes in the Twin Block group. Conclusion:Both the Forsus FRD and Fixed Twin Block appliances are clinically effective for treating Class II Division 1 malocclusion. The choice of appliance should be based on individual patient needs, including compliance and treatment duration. While Twin Block is better suited for skeletal correction, Forsus is advantageous in non-compliant cases due to its fixed nature and shorter treatment time.